A comparative study on the bioavailability of phenolic compounds from organic and nonorganic red grapes. (30th November 2019) - Iglesias-Carres, Lisard; Mas-Capdevila, Anna; Bravo, Francisca Isabel; Aragonès, Gerard; Arola-Arnal, Anna; Muguerza, Begoña
Highlights: Organic growing system affects the phenolic profile of red Grenache grapes. Organic growing system decreases the fibre content of red Grenache grapes. Organic grapes phenolic compounds show a particular bioavailability in rats. Phenolic composition and fibre affect grape polyphenol bioavailability. Abstract: The health-promoting functions of fruit phenolic compounds are mainly attributed to their metabolites. The organic cultivation of fruits is becoming increasingly popular. Thus, this study evaluates whether the differences in red Grenache grapes derived from organic culture conditions influence the bioavailability and metabolism of phenolic compounds in rats. Organic and nonorganic (conventional) red Grenache grapes (OG and CG, respectively) were characterized and administered to Wistar rats (65 mg gallic acid equivalents/kg bw). Serum was recollected at different time points, and the phenolic metabolites were quantified by HPLC-ESI-MS/MS. The results showed that organic cultivation increased the oligomeric proanthocyanidin and anthocyanidin contents and decreased the content of free flavanols and dietary fiber. The serum profile of OG-administered rats showed higher metabolite concentrations at 2 h and reduced metabolite concentration at 24 h compared with the CG-administered rats. Thus, this particular serum kinetic behavior might influence the bioactivity of their phenolic compounds.